2010
DOI: 10.1111/j.1365-2354.2009.01145.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Like a sieve’: an exploratory study on cognitive impairments in patients with multiple myeloma

Abstract: The aim of this study was to obtain a more in-depth understanding of cognitive impairments and concerns as described by patients with multiple myeloma and the strategies used to cope with them. Semi-structured qualitative interviews were undertaken with 15 multiple myeloma patients of differing age ranges and at various stages of their disease. Various cognitive impairments, such as problems with short-term memory, poor recall and lack of concentration were observed and/or expressed in at least 10 out of 15 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
1
21
0
4
Order By: Relevance
“…A sample of the patients' partners (n=93) was also assessed, and it was shown that the partners/ informal caregivers had considerably lower psychological functioning and higher unmet supportive care needs than the patients [17]. Furthermore, in an interview study of 15 myeloma survivors, various cognitive impairments, such as problems with short-term memory, poor recall and lack of concentration, were observed and/or expressed in at least two thirds of the sample, impairments that significantly interfered with personal and professional lives [20]. The low public recognition of this disease, which is diagnosed predominantly in older people coupled with the use of intensive treatments, frequent relapses and poor prognosis, suggest that this group may have different issues and difficulties from other haematological cancers such as lymphomas and leukaemias.…”
Section: Introductionmentioning
confidence: 97%
“…A sample of the patients' partners (n=93) was also assessed, and it was shown that the partners/ informal caregivers had considerably lower psychological functioning and higher unmet supportive care needs than the patients [17]. Furthermore, in an interview study of 15 myeloma survivors, various cognitive impairments, such as problems with short-term memory, poor recall and lack of concentration, were observed and/or expressed in at least two thirds of the sample, impairments that significantly interfered with personal and professional lives [20]. The low public recognition of this disease, which is diagnosed predominantly in older people coupled with the use of intensive treatments, frequent relapses and poor prognosis, suggest that this group may have different issues and difficulties from other haematological cancers such as lymphomas and leukaemias.…”
Section: Introductionmentioning
confidence: 97%
“…The disorders of cognitive processes have already been noted in research on a group of patients with a diagnosed multiple myeloma [27,28]. In case of this cancer, a target therapy can be directed at cytokines, such as interleukin 6, tumor necrosis factor or BDNF neurotrophin, since a crucial part of these biological factors has been observed in tumor progression [23].…”
Section: Chemobrain and Multiple Myelomamentioning
confidence: 99%
“…These compounds turned out to be crucial in development of cancer among the patient with multiple myeloma [29][30][31]39]. Potrat's research from 2010 [28] shows that the incidence of chemobrain phenomenon was observed in case of patients with MM. Then, is it possible to present the connection between particular biochemical factors (TNF-α, IL-6, BDNF) and the changes in the functioning of patients with multiple myeloma?…”
Section: Chemobrain and Multiple Myelomamentioning
confidence: 99%
See 2 more Smart Citations